2020
DOI: 10.1186/s12870-020-02689-6
|View full text |Cite
|
Sign up to set email alerts
|

Two divergent chloroplast genome sequence clades captured in the domesticated rice gene pool may have significance for rice production

Abstract: Background The whole chloroplast genomes of 3018 rice genotypes were assembled from available sequence data by alignment with a reference rice chloroplast genome sequence, providing high quality chloroplast genomes for analysis of diversity on a much larger scale than in any previous plant study. Results Updated annotation of the chloroplast genome identified 13 more tRNA genes and 30 more introns and defined the function of more of the genes. Domesticated rice had chloroplast genomes that were distinct from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, both the reference S. bicolor NC008602 and S. bicolor 112151 are different accessions from different seed sources of the same cultivar Tx623 B (maintainer) whereas S. bicolor 314746 is from the cultivar Tx623 A (male sterile) (Table 1), which are breeding lines of a single variety of Tx623. Recent studies revealed variations within chloroplast genome sequences (Moner et al, 2018(Moner et al, , 2020 that could be associated with multiple domestication events in rice (Oryza sativa L.). Although the nuclear phylogeny places the S. bicolor accessions in one clade, this does not exclude the possibility that more than one chloroplast type from wild progenitors has been captured by domesticated sorghum as has been found in rice (Moner et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, both the reference S. bicolor NC008602 and S. bicolor 112151 are different accessions from different seed sources of the same cultivar Tx623 B (maintainer) whereas S. bicolor 314746 is from the cultivar Tx623 A (male sterile) (Table 1), which are breeding lines of a single variety of Tx623. Recent studies revealed variations within chloroplast genome sequences (Moner et al, 2018(Moner et al, , 2020 that could be associated with multiple domestication events in rice (Oryza sativa L.). Although the nuclear phylogeny places the S. bicolor accessions in one clade, this does not exclude the possibility that more than one chloroplast type from wild progenitors has been captured by domesticated sorghum as has been found in rice (Moner et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed variations within chloroplast genome sequences (Moner et al, 2018(Moner et al, , 2020 that could be associated with multiple domestication events in rice (Oryza sativa L.). Although the nuclear phylogeny places the S. bicolor accessions in one clade, this does not exclude the possibility that more than one chloroplast type from wild progenitors has been captured by domesticated sorghum as has been found in rice (Moner et al, 2020). Multiple domestications or chloroplast capture by reticulate evolution (Jackson et al, 1999) may be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introns, a group of self-catalytic ribozymes that could splice their own excision from mRNA, tRNA, and rRNA precursors, help to infer phylogenetic relationships. The length of exons and introns in genes was important information in plant chloroplast genome 24 , 25 . In this study, there were two genes ( ycf3 and clpP ) including two introns in four Ardisia chloroplast genome.…”
Section: Discussionmentioning
confidence: 99%
“…While much work has been dedicated to understanding the origin and evolution of domesticated rice the issue of multiple versus single origins is a topic of ongoing debate. Most recent studies have concluded that a multiple origin scenario is most likely however the number of domestication events wherein key grain domestication loci were acquired remains unresolved (Huang et al, 2012;Civan et al, 2015Civan et al, , 2019Choi et al, 2017;Choi and Purugganan, 2018;Civan and Brown, 2018;Wang W. S. et al, 2018;Moner et al, 2020). The two major type of cultivated rice, indica and japonica, originated from different ancestral wild rice populations, with gene flows observed from japonica to indica as well as two relatively small ecotypes, aus and aromatic rice.…”
Section: Multiple Primary Origins With Ongoing Selection and Admixture Generate Secondary Origins Resulting In A High Diversity Of Cultivmentioning
confidence: 99%